2017
DOI: 10.24237/djps.1304.341a
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Resistance of Isolated Bacteria from Patients with Urinary Tract Infection

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Another study showed that male & female patients were from the age group 19 to 35 years. 22,23 In our study, figure 3 represents the presences of biolm formers among Escherichia coli, which is approximately 90%, 135 out of 150 isolates. A biofilm is a colony of bacteria living on surfaces enclosed by an extracellular matrix.…”
Section: Discussionmentioning
confidence: 68%
“…Another study showed that male & female patients were from the age group 19 to 35 years. 22,23 In our study, figure 3 represents the presences of biolm formers among Escherichia coli, which is approximately 90%, 135 out of 150 isolates. A biofilm is a colony of bacteria living on surfaces enclosed by an extracellular matrix.…”
Section: Discussionmentioning
confidence: 68%